An analysis of regular training programs and related human resources practices of BRAC learning and leadership development unit - Anik, Md. Jehad Sarker (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.